MODELING PROJECTIONS OF THE DEPENDENCY RATIO OF THE NON-PRODUCTIVE AGE POPULATION TO THE PRODUCTIVE AGE POPULATION IN EAST JAVA PROVINCE - Arini, Audi Cindra; Frizqy, Zea Zildha Nadya; Khumairah, Mutiari; Putri, Rany Riandhani (GEOREFERENCE, 2024)
The understanding of demographic trends, particularly in terms of population dependency ratios, is crucial for formulating responsive and sustainable policy. This research employs a descriptive quantitative method using data from the number of inhabitants based on age in Jawa Timur from 2015 to 2022, projected to 2023 to 2030. The data analysis is performed using arithmetic and geometric methods. According to the arithmetic population projection method, the relative increase in population remains constant each year. On the other hand, the geometric method, which is the second method, assumes that population growth will increase geometrically using a compound interest formula. However, both population projection methods result in decreasing dependency ratios each year. Using the arithmetic method, the increase in the working-age population remains stable. In contrast, the geometric method indicates an increase in the working-age population each year, resulting in a higher annual growth rate. For non-productive age groups, both methods are classified as low growth rates, as the results are less than 1%. This projection provides a foundation for understanding demographic trends that are essential for policy planning and development in the future.